Empowerment of Farmers Through the Field School Program Integrated Rice Crop Management. A Study of Farmer Groups at Desa Linamnutu , Kecamatan Amanuban Selatan, Kabupaten Timor Tengah Selatan - Febrianto Nenes; Charles Kapioru; Ignatius Sinu (Undana Press, 2022)
This study aims to determine (1) the extent of the integrated crop management field school program in farmer groups through human development,capital development, institutional development. (2) know the level of success of the field school program integrated rice crop management to increase productivity and income of farmers in the farmer groups in the village linamnutu Amanuban southern sub-district , east middle south. The method used is the survey method. The location was determined deliberately ( purposive sampling ) namely linamnutu village, south amanuban district, south central timor regency. The population of this study is the farmer groups involved in the field school program for integrated crop management namely : Taubtit farmer group, Brother farmer group, one-year peasant group and 63 members. Farmer samples are determined by proportional random sampling with the slovin formula, so that a sample of 39 farmers is obtained. The analysis used in this research is descriptive qualitative and the average analysis uses a Likert scale approach. The results of the study note that 72% of respondents belong to productive adulthood and 28% of non-productive age (>55) years. Formal education is classified as low (38%) of the total respondents ie educated to graduate from elementary scholl ), non-formal education (100%), and farm area is at intervals >0,5 Ha, Which is 74%. The field school integrated crop management field program has succeeded in applying the technology component of lowland rice cultivation, and is in the “High” category with an average score of 100%. Farmer business development in Linamnutu village increased by applying the cultivation technology component and was in the “ High” category with an average of 90.29%. Farmer capital development in linamnutu village increases by applying the technology component of rice cultivation and is in the “High” category with an average score 98.86%. Institutions in the village of Linamnutu improved by applying the technology component if rice cultivation to be in the “ Dynamic “ category with an average score of 93.89%.